Teachers' Work Ethic from an Islamic Perspective in Meeting the Challenges of the Digital Age - Sucipto, Joni Hadi (PT. Publikasiku Academic Solution, 2026)
Digital transformation has brought existential challenges to the world of education, in which the role of teachers is increasingly confronted with technological disruption, a crisis of scholarly authority, and the phenomenon of digital burnout. This research aims to explore and reconstruct the concept of teachers' work ethics from the perspective of the Qur'an and to actualize it as a strategy for facing the challenges of the digital era. Through a library research method with a qualitative approach and the technique of thematic interpretive analysis (tafsir maudhu'i), this study examines various classical and contemporary sources to arrive at a synthesis between the values of divine revelation and the demands of modern professionalism. The findings reveal that the Qur'an provides four pillars of teachers' work ethics: itqan (professionalism), amanah (integrity), mujahadah (resilience), and iqra' (continuous learning). This Qur'an-based work ethic functions as a